Valorisation of microalgae residues after lipid extraction: Pyrolysis characteristics for biofuel production - Huang, Zhigang; Zhang, Jiang; Pan, Minmin; Hao, Yuhang; Hu, Ruichen; Xiao, Wenbo; Li, Gang; Lyu, Tao (Elsevier, 2021)
As a promising source of renewable energy, biofuel from microalgae pyrolysis is seen as a competitive alternative to fossil fuels. However, currently, the widely applied pre-treatment process of lipid extraction results in large amounts of microalgae residues, which though with energy potential, being considered as process wastes and ignored of its re-utilization potential. In this study, a new workflow of biofuel generation from microalgae biomass through lipid extraction and pyrolysis of defatted microalgae residues was proposed and assessed. The effects of lipid extraction and pyrolysis temperature (350–750 ℃) on pyrolysis products were investigated, and pyrolysis pathways were postulated. To address the twin goals of lowering emission of pollutants and elevating energy products, an optimal pyrolysis temperature of 650 ℃ was suggested. After extraction of lipids, the relative contents of valuable products (aromatic, aliphatic hydrocarbons and fatty acids) and some harmful by-products, e.g., PAHs, significantly reduced, while other harmful substrates, e.g., nitrogen-compounds increased. Mechanistic investigations indicated that pyrolysis of proteins without the presence of lipids could promote higher production of nitrogen-containing organics and aromatics. These results reveal the effects of lipid extraction and variation of temperature on microalgal pyrolysis, and also provide a basis for full utilization of microalgae as an aid to alleviate many fossil energy problems.
Keywords: Bioenergy; Pyrolysis pathways; Net-zero emission; Microalgae technology; Circular economy